Analisis Kebijakan Kesetaraan Gender Dalam Meningkatkan Kepuasan Pegawai Dinas Perhubungan Kota Gunungsitoli - Meiman jaya hulu; Odaligoziduhu Halawa; Eliyunus Waruwu; Meiman Hidayat Waruwu (Visi Sosial Humaniora, 2024)
Hulu, Meiman Jaya. 2023. Analysis of Gender Equality Policy in Improving Employee Satisfaction at the Transportation Agency of Gunungsitoli City. Thesis. Supervisor: Odaligoziduhu Halawa SE., M.M. The research is motivated by the challenges and opportunities related to gender equality and the empowerment of women in the environment of the Transportation Agency of Gunungsitoli City. With a focus on women's participation in employment and positions within the structure, strategic decision-making, and working conditions, the research seeks to identify the possible limitations faced in efforts to enhance gender equality. The study aims to delve into the issues of gender equality and women's empowerment in the Transportation Agency of Gunungsitoli City, focusing on women's participation in structural positions, strategic decision-making, and working conditions. Through a qualitative approach involving secondary data analysis and in-depth interviews, the research reveals limitations in comprehensive data access related to women's participation at various organizational levels. The research methodology used is descriptive qualitative, involving data collection through observation and interviews with female employees and structural leadership in the Transportation Agency of Gunungsitoli City. The findings of this research recommend the development of more specific empowerment programs, provision of specialized support and training, and the integration of gender equality in organizational policies. The conclusion of the study is that the Transportation Agency of Gunungsitoli City has provided access support to female employees, but further efforts are needed to enhance women's involvement and training development. Therefore, it is expected that the findings of this research can help formulate more effective strategies in supporting gender equality and women's empowerment in the workplace.